THE USE OF MIND MAP IN IMPROVING STUDENTS' READING COMPREHENSION(A CLASSROOM ACTION RESEARCH AT X-7 SMA KARTIKA SILIWANGI I BANDUNG) - Rissa San Rizqiya, - (2010)
Mind map is one of the techniques that can increase one's ability in note taking. It not only includes the key words of information or idea but also implements the use of colours and draws thus the mind mapping project becomes fun and enjoyable. Therefore mind map was considered to be an alternative technique to improve students reading ability in SMA Kartika Siliwangi I Bandung, especially in X-7. From initial observation, it was found that the students' reading comprehension was poor. In order to reveal the problem, a classroom action research was conducted. This study consisted of three cycles. During the study, observation and reflection sheets, students' mind maps, and pre and post test scores were used as instruments. The data that had been collected was analysed through scoring technique and descriptive study. Through comparing their pre-test (mean= 50.56) and post-test (mean= 80.12) scores, there is an improvement on students comprehension. It is also found that the students were not realized that they practiced their reading comprehension. Additionally, their creativity developed as well; since the use of colour and draw was also developed. There were no significant difficulties in conducting this technique as long as the teacher was well prepared.